Evaluation, Exploration and Management Strategies of a First Reported Rarest Case of Para-Bombay Blood Phenotype with E-Beta Thalassaemia from Bangladesh - Dipta, Tashmim Farhana; Kabir, Amin Lutful; Quader, Mohammed Abdul; Parvin, Farida; Khatun, Ayesha (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Human H/h genetic polymorphism in ABO blood group system is rare and evidenced with Bombay and Para-Bombay blood group. This patient a 27-year-old-young man having ‘E-Beta thalassaemia’ incidentally has been identified as a case of ‘Para-Bombay phenotype’ after exploring with proper blood grouping, antibody detection and saliva inhibition study. Previously he was diagnosed as ‘O’ RhD positive and had two events of transfusion reaction during ‘O’ positive blood transfusion. In literature search and browsing there is dearth information on Para-Bombay Phenotype with E-Beta Thalassaemia. So far to our knowledge, this is the first reported case from Bangladesh of patient having ‘E-Beta Thalassaemia’ evidenced with rare ‘Para-Bombay blood Phenotype’. This study explores the laboratory work-out on Para-Bombay Phenotype and evaluates treatment strategies on this phenotype with concomitant E-Beta Thalassaemia. J Bangladesh Coll Phys Surg 2024; 42: 97-104